Purifying the 1920s Southern American Society: The Grotesque in Flannery Oâ€™Connorâ€™s â€œA Good Man is Hard to Findâ€ - Windriani, Dian (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2018)
Flannery Oâ€™Connorâ€™s â€œA Good Man is Hard to Findâ€ (1953) criticizes the experience of humanâ€™s isolation, vanity, and disillusionment in Southern America under political instability, dictatorial regime, hypocrisy of the church and high number of poverty that can lead to the crisis of faith and humanity in peopleâ€™s life. By presenting the violence, horror, and emotional freak in the story, Oâ€™Connor wishes that the characters can come to their self-realization upon their faith and humanity. This paper finds out that the portrayal of grotesque character in â€œA Good Man is Hard to Findâ€ can be seen as a mechanism to purify the Southern American society in the twentieth century that has already been far away from their religious belief.Â Keywords: Grotesque, Purification, Southern America, Flannery Oâ€™Connor